The Impact of the New Public Service Model (NPS) on the Organizational Efficiency: A Field Study on the Saudi Ground Services Company - Alshehri, Afnan Mohammed; Alqurashi, Suzan Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to understand the impact of the New Public Service Model with its dimensions (Service Quality, Accessibility, Reliability) on Organizational Efficiency with its dimensions (Objectives Achievement, Cost Savings) in the Saudi Ground Services Company. The study used the survey (descriptive correlational) approach, the population included all employees of the studied company (leaders, administrative staff, and passenger service agents), totaling 3,885 individuals. The researcher relied on simple random sampling due to the large population, which indicated that the required sample size was 350 individuals from the population. A questionnaire was used as a data collection tool. The findings of this study showed that the reality of applying the New Public Service in the studied company is high, with an overall mean of (3.66 out of 5.00) and a relative weight of (73.2%). Also, the reality of Organizational Efficiency in the studied company is moderate, with an overall mean of (3.22 out of 5.00) and a relative weight of (64.4%). There is an impact of the New Public Service Model on Organizational Efficiency in the studied company, with a correlation coefficient of (0.666). There is no statistically significant relationship between the sample individuals’ responses on the study variables according to personal and functional variables represented by: gender, age, years of experience, educational qualification, and marital status. The study recommends working effectively on the integration of New Public Service dimensions to sustain successes and improvements in the company and increase efficiency as it serves as a "face of the nation".